P376 Efficacy of ozanimod in vedolizumab-exposed patients with ulcerative colitis: a phase 3 True North post hoc analysis. (30th January 2023) - Sands, B E; Jain, A; Ahmad, H A; Osterman, M; Memaj, A; Canavan, J B; Axelrad, J E
Abstract: Background: Ozanimod (OZA), an oral sphingosine 1-phosphate receptor modulator that prevents lymphocyte migration to inflamed tissues, is approved for the treatment of patients with moderate to severe ulcerative colitis (UC) in the European Union and United States. The phase 3 True North (TN) randomised trial showed that OZA was effective and well tolerated in these patients. OZA efficacy in patients who have been exposed to vedolizumab (VDZ-exp), an integrin receptor antagonist that interferes with lymphocyte trafficking to the gut, has not yet been described. This post hoc analysis of TN examined OZA efficacy in VDZ-exp patients. Methods: In TN, patients were randomised to oral once-daily OZA 0.92 mg (equivalent to OZA HCl 1 mg) or placebo (PBO; Cohort 1) or to open-label OZA (Cohort 2) during the induction period (IP). Patients with a clinical response to OZA at Week 10 were rerandomised to OZA or PBO in the maintenance period (MP). Efficacy at Week 10 (IP) and Week 52 (MP) in the VDZ-exp subgroup was calculated. Differences in proportions between OZA and PBO at Week 10 were based on the Cochran-Mantel-Haenszel (CMH) test, stratified by corticosteroid use at screening and prior anti-tumor necrosis factor (anti-TNF) use. Differences between OZA/OZA and OZA/PBO at Week 52 were based on the CMH test stratified by both remission status and corticosteroid use at Week 10. Results: TN included a total of 185 VDZ-exp patients (Cohort 1: PBO, n=35; OZA, n=63; and Cohort 2: OZA, n=87). Baseline demographics and clinical characteristics were balanced across treatment groups. In the VDZ-exp subgroup, 52% of patients had extensive disease at baseline, 78% had a Mayo endoscopic score of 3, 85% were previously exposed to anti-TNF, and 61% were receiving corticosteroid at baseline. At Week 10, OZA (Cohort 1) was numerically more effective vs PBO for all endpoints in VDZ-exp pts (Figure 1A). Notably, in the subgroup of patients previously exposed to VDZ as a first-line advanced therapy, clinical response at Week 10 was achieved in 50% (6/12) of OZA pts in Cohort 1 and 42% (5/12) of OZA patients in Cohort 2. At Week 52, a higher proportion of VDZ-exp patients on continuous OZA achieved all efficacy endpoints vs the OZA/PBO group, with significant differences shown for most endpoints. OZA/OZA vs OZA/PBO differences at Week 52 were larger than OZA vs PBO differences at Week 10 (Figure 1B). Conclusion: This post hoc analysis of the phase 3 TN study found that OZA was effective in UC patients who previously failed VDZ, including those who failed VDZ alone or following other advanced therapies. Future studies evaluating OZA in VDZ-exp patients are warranted.